Influences of organizational climate, transformational leadership on employees’ emotional exhaustion, organizational citizenship behavior in real estate enterprises - Nguyen, Kieu Oanh; Mai, Thoai Diem Phuong; Tran, The Nam; Nguyen, Thi Kim Ba; Mai, Thanh Huong (Journal of Finance - Marketing Research, 2023)
In a business with strong competition as real estate, how to limit emotional exhaustion and increase organizational citizenship behavior of employees is an interesting question. Based on the theory of social exchange, the authors investigate the impact of organizational climate, transformational leadership on emotional exhaustion, organizational citizenship behavior of employees in real estate business. The qualitative research method was used to build the research model. The quantitative research method with partial least squares structural equation modeling (PLS-SEM) was used to analyze data of 193 employees in the real estate business. The results showed that both organizational climate and transformational leadership increase organizational citizenship behavior. However, while transformational leadership alleviates emotional exhaustion, the organizational climate enhances it. In practice, leaders need to have flexibility in leadership styles as well as businesses need to improve the working environment to help reduce employee fatigue and improve virtue civic behaviors.